Uso de las metodologías activas planteadas en la guía de apoyo para los docentes en la implementación de metodología STEM - STEAM en la unidad educativa fiscomisional Calasanz en el año lectivo 2022 - 2023 - Vásquez Ramón, Andy Javier (2024)
Currently, applying new methodologies that innovate and strengthen the teaching-learning process is fundamental in the teaching practice and for all educational actors, for this reason, this research aims to diagnose the use of active methodologies proposed in the support guide for teachers in the implementation of STEM - STEAM methodology in the Calasanz Fiscomisional Educational Unit in the school year 2022 - 2023. The research methodology had as its basis the deductive method, with a quantitative approach, of descriptive scope and cross-sectional study design. The active methodologies used by teachers in the classroom are defined, achieving identifying five active methodologies from the STEM - STEAM guide of the Ministry of Education of Ecuador (2021), which refer to project-based learning, problem-based learning, inverted classroom, cooperative learning and gamification. Under other references, nine active methodologies were identified bibliographically that can be employed by educators, with the objective of supporting the formative process of students, which are: Challenge-based learning, service-learning, inquiry-based learning, research-based learning, design thinking, recommended by different authors to support the formative process of students; in the same sense, the characteristics and description of each of them have been described, highlighting that these enhance active participation in the student and strengthen their learning skills, thus evidencing a basis for future research in the educational context. Keywords: Active methodologies, stem-steam methodology, gamification, inverted classroom.